Good practices in reforming the common agricultural policy to support the European Green Deal: A perspective on the consumption of pesticides and fertilizers - Alina Petronela Alexoaei; Raluca Georgiana Robu; Valentin Cojanu; Dumitru Miron; Ana-Maria Holobiuc (Amfiteatru Economic Journal, 2022)
Against the background of the goals of the European Green Deal to reduce the use of pesticides by 50% and fertilizers by 20% by 2030, the current analysis aims to: (1) identify key economic, institutional, and legislative levers that can play an important role in the agricultural specialization of the EU according to the European Green Deal and the reform of the Common Agricultural Policy; (2) analyze representative variables of the European agricultural environment during the 2000-2019 period concerning the alignment of Member States with the objectives of the Green Deal and the overall performance of the agricultural sector; (3) present a set of good practices to reduce the use of fertilizers and pesticides in agricultural systems based on the documentation of the impact of these substances on human health and the environment. The results show that available agricultural solutions, in line with the objectives of the Green Deal and the Common Agricultural Policy, are effective in practice. Our findings can help define national sustainable production policies and develop practical measures for farmers and companies in the agricultural industry.
Keywords: Q01; Q56; 330; best practices; European Green Deal; inorganic fertilizers; pesticides; sustainable crop production.